Biogeographic Patterns of Finnish Crane Flies (Diptera, Tipuloidea) - Jukka Salmela (Psyche: A Journal of Entomology)
Species richness of terrestrial and freshwater biota generally decreases with increasing latitude. Some taxa, however, show an anomalous species richness pattern in a regional or global scale. The aim of this study was to examine (i) regional variation in species richness, (ii) faunistic composition, (iii) occupancy, and (iv) proportions of different distribution types of Finnish crane flies. Analyses were based on incidence data pooled into 20 biogeographical provinces. Finnish crane fly fauna consists of 335 species; the provincial richness varies from 91 to 237. The species richness of all species and saproxylic/fungivorous species decreased with increasing latitude; mire-dwelling crane flies displayed a reversed pattern (Spearman's correlations). Thirty-one species occupied a single province and 11 species were present in all provinces. Provincial assemblages showed a strong latitudinal gradient (NMS ordination) and faunistic distance increased with increasing geographical distance (Mantel test). Nearly half (48%) of the Finnish crane flies are Trans-Palaearctic, roughly one-third (34%) are West Palaearctic, and only 16 and 2% are Holarctic and Fennoscandian, respectively. Endemic Fennoscandian species are discussed in detail; most likely there are no true endemic crane flies in this region.